Pengaruh Tipe Kepeminpinan Terhadap Semangat Kerja Pegawai Pada Sekretariat Daerah Kota Gorontalo - Abdul Latif; Luqmanul Hakiem Ajuna (Al-Buhuts, 2020)
The study aims to find out how much influence the type of leadership on employee morale at the Gorontalo city regional secretariat, sampling technique with a minimal sample so that the sample size is 54 people. Collecting basic data through a list of questions tested through two stages, namely the validity test and the reliability test for each question item contained in the questionnaire. The analytical method used is path analysis. Leadership types in the form of autocratic type, charismatic type and democratic type are proven to have a positive and significant effect on employee morale, the simultaneous effect of leadership type variables on employee morale is 60.9%. The calculation shows that there are still effects of other variables outside the leadership type variable that affect employee morale around 39.1%. The partial influence of the leadership type sub variable on employee morale shows that the democratic type sub variable is the variable with the greatest influence, which is 46.6%. Furthermore, the autocratic type is a sub variable that influences the second rank after the democratic type of employee morale which is 28.6%. This contribution shows a very low effect compared to the other sub variables. The third sub variable of the type of leadership that influences morale is the charismatic type. The magnitude of the influence of charismatic type on morale is 19.8%.